Can Violence Be Thought? Notes on Badiou and the Possibility of (Marxist) Politics: Може ли да се мисли насилството? Размисли за Бадју и за можноста за (марксистичка) политика - Toscano, Alberto; Čemerski, Ognen (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Alberto Toscano | Алберто Тоскано Title (English): Can Violence Be Thought? Notes on Badiou and the Possibility of (Marxist) Politics Title (Macedonian): Може ли да се мисли насилството? Размисли за Бадју и за можноста за (марксистичка) политика Translated by (English to Macedonian): Ognen Čemerski | Огнен Чемерски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-38 Page Count: 29 Citation (English): Alberto Toscano, “Can Violence Be Thought? Notes on Badiou and the Possibility of (Marxist) Politics,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 9-38. Citation (Macedonian): Алберто Тоскано, „Може ли да се мисли насилството? Размисли за Бадју и за можноста за (марксистичка) политика“, превод од англиски Огнен Чемерски, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 9-38.